The first report of the genus Deutereulophus Schulz (Hymenoptera: Chalcidoidea: Eulophidae) from Korea, with a redescription of D. malabarensis Narendran - Bae, Jongmin; Jung, Sunghoon (Journal of Asia-Pacific biodiversity, 2021)
The genus Deutereulophus Schulz (Hymenoptera: Eulophidae) is newly recognized from South Korea. Until this study, there were only two species from the Palearctic region; D. brevipennis and D. tennysoni. We report the genus Deutereulophus from Korea for the first time with D. malabarensis with its illustrations and redescription. In addition, a key to the species of the Palearctic Deutereulophus is also provided.